DNA replication: Mechanisms and therapeutic interventions for diseases. Issue 1 (5th February 2023) - Song, Hao‐Yun; Shen, Rong; Mahasin, Hamid; Guo, Ya‐Nan; Wang, De‐Gui
Abstract: Accurate and integral cellular DNA replication is modulated by multiple replication‐associated proteins, which is fundamental to preserve genome stability. Furthermore, replication proteins cooperate with multiple DNA damage factors to deal with replication stress through mechanisms beyond their role in replication. Cancer cells with chronic replication stress exhibit aberrant DNA replication and DNA damage response, providing an exploitable therapeutic target in tumors. Numerous evidence has indicated that posttranslational modifications (PTMs) of replication proteins present distinct functions in DNA replication and respond to replication stress. In addition, abundant replication proteins are involved in tumorigenesis and development, which act as diagnostic and prognostic biomarkers in some tumors, implying these proteins act as therapeutic targets in clinical. Replication‐target cancer therapy emerges as the times require. In this context, we outline the current investigation of the DNA replication mechanism, and simultaneously enumerate the aberrant expression of replication proteins as hallmark for various diseases, revealing their therapeutic potential for target therapy. Meanwhile, we also discuss current observations that the novel PTM of replication proteins in response to replication stress, which seems to be a promising strategy to eliminate diseases. Abstract : Accurate DNA replication is modulated by multiple replication‐associated proteins, which is fundamental to preserve genome stability. Abundant replication proteins are involved in tumorigenesis and development, implying these proteins act as therapeutic targets in clinical. Replication‐target cancer therapy emerges as the times require. Furthermore, the novel posttranslational modification of replication proteins in response to replication stress, which seems to be a promising strategy to eliminate diseases.